My happy marriage. 3 - Agitogi, Akumi (Square Enix Manga, 2023)
A Cinderella-inspired, slow-burn historical romance with a paranormal twist set in Taisho-era Japan! A browbeaten and mistreated daughter is cast out of her home and sent to audition as a bridal candidate for the heir to one of the most powerful families in the land... For failing to inherit the boon of unusual power that is the Saimori birthright and bringing shame to the family name, mistreated Miyo is cast out to become another's problem. Sent to the Kudo clan--itself preternaturally powerful--as a potential bride for its heir, Kiyoka, Miyo is surprised to experience kindness for the first time in her thus far sad life. Though the rumors make him out to be cold and haughty, Kiyoka Kudo quickly warms up to the Saimoris' eldest daughter. Intrigued by the girl who stands worlds apart from the spoiled, social-climbing women who usually vie for his hand, Kiyoka soon comes to regard Miyo with affection. Just as Miyo believes she may have found happiness at last, her jealous half sister, Kaya, kidnaps her and locks her in a cellar. Kaya's eyes are red with rage as she declares her intention to dissolve Miyo's engagement to Kiyoka and replace Miyo as his fiancée herself! Will Kiyoka's supernatural abilities deliver her from Kaya's clutches in time?